Comprehensive assessment and forecast of sustainable development of rural areas of the Karaganda region - Komekbaeva, L.S.; Akbaev, E.T.; Abaev, A.A.; Topshahova, G.R. (BUKETOV BUSINESS REVIEW, 2022)
Object: Тo study the theoretical and methodological foundations and substantiate scientific and practical proposals for increasing the organizational and economic potential of sustainable development of rural areas, development of a model of multiple regression with a forecast of sustainable development of rural areas in the Karaganda region. Methods: Abstract-logical, statistical, expert, comparative and structural methods. Results: The management of Labor Relations in rural areas is currently a key part of strategic directions, that is, effective management of inter-farm sectors, effective production and socio-economic relations between economic entities. Today, agricultural workers have full ownership of land and legal relations with the means of production, as a result of which they have the opportunity to sell Economic products. This issue affects the development of inter-farm production and economic relations. Conclusions: Rural areas with a low level of development have few opportunities to attract investment, and the positive dynamics of socio-economic development determine a high level of economic potential. Based on these positions, it is possible to form a system of indicators that characterize the economic development of rural areas (indicators of budget stability, indicators of production potential and indicators of investment potential). The developed system of indicators allows us to assess the effectiveness of measures to improve the production and investment potential of rural areas based on the analysis of statistical and operational information, provide targeted budget support aimed at sustainable development of territories.